2018
DOI: 10.1124/dmd.117.077511
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolism and Disposition of a Novel Selective α7 Neuronal Acetylcholine Receptor Agonist ABT-126 in Humans: Characterization of the Major Roles for Flavin-Containing Monooxygenases and UDP-Glucuronosyl Transferase 1A4 and 2B10 in Catalysis

Abstract: Mass balance, metabolism, and excretion of ABT-126, an 7 neuronal acetylcholine receptor agonist, were characterized in healthy male subjects ( = 4) after a single 100-mg (100 Ci) oral dose. The total recovery of the administered radioactivity was 94.0% (±2.09%), with 81.5% (±10.2%) in urine and 12.4% (±9.3%) in feces. Metabolite profiling indicated that ABT-126 had been extensively metabolized, with 6.6% of the dose remaining as unchanged parent drug in urine. Parent drug accounted for 12.2% of the administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In a survey of enzymes involved in the metabolism of the FDA new drug applications between 2013 and 2016, FMO enzymes were listed as contributing to the metabolism of only 3 out of 98 cases (where data were available) and investigation with clinical DDI studies was not reported for any of these (Yu et al, 2018). FMOs are generally viewed favorably as contributing enzymes to the metabolism of drugs, recently reiterated in the case study for ABT-126 which is mainly metabolized by FMOs (Liu et al, 2018). FMO induction is not well-known and few drugs which inhibit FMOs have been identified, reducing the likelihood of DDIs (Cashman and Zhang, 2006).…”
Section: Investigating the Combination Of Cyp P450 And Flavin-containing Monooxygenase Contributions To Risdiplam Metabolism And Implicatmentioning
confidence: 99%
“…In a survey of enzymes involved in the metabolism of the FDA new drug applications between 2013 and 2016, FMO enzymes were listed as contributing to the metabolism of only 3 out of 98 cases (where data were available) and investigation with clinical DDI studies was not reported for any of these (Yu et al, 2018). FMOs are generally viewed favorably as contributing enzymes to the metabolism of drugs, recently reiterated in the case study for ABT-126 which is mainly metabolized by FMOs (Liu et al, 2018). FMO induction is not well-known and few drugs which inhibit FMOs have been identified, reducing the likelihood of DDIs (Cashman and Zhang, 2006).…”
Section: Investigating the Combination Of Cyp P450 And Flavin-containing Monooxygenase Contributions To Risdiplam Metabolism And Implicatmentioning
confidence: 99%